STUDENT MOTIVES TO WATCH SPORTS NEWS PROGRAM "GALERI SEPAK BOLA INDONESIA" ON TRANS7 - Yudha, Aria Rusandi; Anggraini, Rosita; Guntur; Yulianto, Kresno (TRANSFORMATIONAL LANGUAGE, LITERATURE, AND TECHNOLOGY OVERVIEW IN LEARNING, 2022)
This study aims to determine students' motives for watching the sports news program “Galeri Sepak Bola Indonesia” on Trans7. This research employs the theories of uses and gratification, as well as individual differences. In this study the dimensions used include information motives, personal identity motives, integrity and social interaction motives, and entertainment motives. This study uses a quantitative approach, with research methods through surveys, the population of respondents is Stikom Interstudi students majoring in broadcasting class of 2016-2018, totaling 141 people. Using a technique of purposive sampling, we asked respondents whether they had watched the program "Galeri Sepak Bola Indonesia" on Trans7 at least twice in the previous month before they were allowed to complete out our questionnaire, thus we obtained 80 students as respondents. The results showed that the motive for watching the “Galeri Sepak Bola Indonesia” program for Stikom Interstudi students was mostly information motives, from the 4 dimensions of the existing research results.